2014
DOI: 10.7763/ijesd.2014.v5.502
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Some Physico-Chemical Parameters and Biodiversity of Gastropods Species in Euphrates River, Iraq

Abstract: Abstract-The biodiversity of some Gastropods taxa were studied in three selected stations in Euphrates River middle of Iraq (Musayb; Saddat Al-hindya and Hindya city) from October 2011 to September 2012.Some Physico-chemical parameters( air &water temperature; pH; TDS; TSS; DO;BOD5; Total harhness) of water in this stations were estimated which have been calculated some biodiversity indices of the of Gastropods species in the study area. Five species of gastropods were recorded, and their density was varied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Mizhir et al (2014) found in Shatt al-Kufa/ Euphrates river all the species that appeared in the current study except for Physa acuta and Th eodoxus jordani. As for Salman and Nassar (2014), they recorded fi ve species of gastropods, which are Melanopsis costata, Melanopsis subtingitana Annandale 1918, Melanopsis nodosa, Melanoides tuberculata and Viviparus bengalensis (Lamarck, 1822) in the Euphrates river at central Iraq. Hashim and Al-Taee (2015) recorded seven species of gastropods (Melanopsis costata, Melanoides tuberculata, Cerithidea cingulate (Gmelin, 1791), Th eodoxus jordani, Hydrobia ventrosa (Montagu, 1803), Lymnaea auricularia and Physa acuta) and three species of bivalves (Laevicardium fl avum (Linnaeus, 1758), Corbicula fl uminea and Unio tigridis) in Al-Razzaza Lake in Karbala province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mizhir et al (2014) found in Shatt al-Kufa/ Euphrates river all the species that appeared in the current study except for Physa acuta and Th eodoxus jordani. As for Salman and Nassar (2014), they recorded fi ve species of gastropods, which are Melanopsis costata, Melanopsis subtingitana Annandale 1918, Melanopsis nodosa, Melanoides tuberculata and Viviparus bengalensis (Lamarck, 1822) in the Euphrates river at central Iraq. Hashim and Al-Taee (2015) recorded seven species of gastropods (Melanopsis costata, Melanoides tuberculata, Cerithidea cingulate (Gmelin, 1791), Th eodoxus jordani, Hydrobia ventrosa (Montagu, 1803), Lymnaea auricularia and Physa acuta) and three species of bivalves (Laevicardium fl avum (Linnaeus, 1758), Corbicula fl uminea and Unio tigridis) in Al-Razzaza Lake in Karbala province.…”
Section: Discussionmentioning
confidence: 99%
“…Th e Euphrates River is passing through eight provinces from the west, centre, and south of Iraq, the river water are fresh with a steady increase in salinity to the south. Some studies on Euphrates river or its branches, which focused on studying Mollusca including (Al-Fanharawi and Ibrahim, 2014;Salman and Nassar, 2014;Ghulam, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Eighty-five percentage (85%) of the reviewed publications did not provide any information about sampling sites selection process. The other reviewed publications used the barrages along the river as a sampling site, such as Al-Hindia and Al-Ramadi barrages (8), (19) and other authors selected the river discharge gaging stations as a sampling site, such as Qaiam and Kufa (6) (31). 93% of the analyzed publications collected the water samples from more than one sampling site and 7% sampled water from one sampling site ( 6), (31), Figure 3.…”
Section: Selection Of Sampling Sitesmentioning
confidence: 99%
“…The gastropod snail Bellamya bengalensis has been studied in Iraqi freshwaters such as in Euphrates and Shatt AL-Arab River [18], and this snail lives in muds or deposit in estuaries [19]. [20], has studies the relationship between biodiversity of gastropods and some physico-chemical factors in sites in Euphrates River. five species of snails Viviparus bengalensis, Melanopsis costata, Melanopsis nodosa, Melanopsis subtingitana, Melanoides tuberculata are found in study areas.…”
Section: Introductionmentioning
confidence: 99%